Pengaruh Inovasi Produk Dan Harga Terhadap Keputusan Pembelian Mobil Kia Sonet Di Showroom Indomobil Gatot Subroto Medan - Rice Triliani Gulo; Purba, Mery Lani; Elisabet Tambunan (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
The aim of this research is to determine the influence of product innovation and price on purchasing decisions for KIA Sonet cars at the Indomobil Gatot Subroto Medan Showroom. This type of research is causal associative research. The data collection technique in this research was carried out by distributing questionnaires to 81 respondents at that showroom using a non-probability sampling method with accidental sampling type. The data analysis technique used is Multiple Linear Regression Analysis. The results of hypothesis testing using the t test show that the two independent variables (product innovation; price) studied were proven to have a positive and significant effect on the dependent variable (purchasing decisions). Then, through the F test, it can be seen that the two independent variables (product innovation; price) studied have proven to have a positive and significant effect on the dependent variable (purchasing decisions). Together, product innovation and price have a significant influence on purchasing decisions. The R² coefficient of determination value of 0.571 means 57.1%, the purchasing decision variable can be explained by the two independent variables in the regression equation. Meanwhile, the remaining 43% is explained by other variables outside the two variables used in other research.